Mathematical competencies of grade five pupils : basis for remediation strategies - Fruto-Flores, Girlie (Manila : National University, 2012)
Researches in the field of education showed that Mathematics consistently obtained the lowest rating in any achievement or aptitude test both local and abroad. Factors were identified but no one is certain which of the following factors is dominant in influencing elementary pupils' performance in Mathematics.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of tables -- List of figures -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.